Effect of Swimming on the Induction of Vitellogenin in Conger Eel (Conger myriaster) - Liu, Rucong; Li, Kang; Wang, Guixiang; Jiang, Zhixin; Ba, Xubing; Liu, Liping (Frontiers in Marine Science, 2022)
Vitellogenin (VTG) plays a very important role in the development of oocytes. This study aims to explore the effect of swimming on the VTG synthesis of conger eel (Conger myriaster). Circulating water flow and hormone injection regimen were two factors set in the following trials: A1 (no injection, no water flow), A2 (no injection, water flow), B1 (injection, no water flow), and B2 (injection, water flow). The flow velocity of the flowing water was 0.4 m/s (12 h, 60 days). We examined VTG, estrogen receptor (Er) gene expression, and VTG content in the liver and serum on the 30th and 60th days. VTG gene expression in A1 and A2 gradually decreased and was not significantly different between the two groups. The expression of Er gene in A1 was significantly higher than that in A2. The expression of VTG gene in group B1 was significantly higher than that in group B2, whereas the expression level of Er gene in group B1 was slightly higher than that in group B1. The VTG content in the liver in group B1 reached 1,396.93 μg/L, which was significantly higher than that in group B2 (1,302.06 μg/L). Results showed that the flowing water factor can inhibit the expression of VTG and Er genes in the liver and reduce the synthesis of VTG in the liver. Stimulation of flowing water can inhibit the yolk accumulation during the ovarian development of conger eel.